Assessing the efficacy and safety of pentoxifylline in preventing chemotherapy-induced peripheral neuropathy and mucositis in breast cancer patients - Dewidar, Samar A.; Mansour, Noha O.; Hamdy, Omar; Eltantawy, Ahmed; Soliman, Moetaza M.; Shams, Mohamed E. E. (Frontiers in Pharmacology, 2025)
BackgroundPentoxifylline (PTX) has demonstrated potential in alleviating several adverse effects induced by chemotherapy in preclinical and limited clinical investigations. Nonetheless, its efficacy in mitigating the overall toxicity associated with doxorubicin, cyclophosphamide, and taxane (AC/T) regimen in breast cancer patients remains uncertain.MethodologyThis study is an open labelled clinical trial in which the participants were randomly assigned to receive either PTX (400 mg three times daily) with the standard chemotherapy regimen or standard chemotherapy alone. The outcomes of the present study include the occurrence of grade 2 or higher peripheral sensory neuropathy and mucositis evaluated according to common terminology criteria for adverse events (CTCAE v5.0).ResultsA total of 106 patients completed the study (PTX: 52; control: 54). The incidence of grade 2 or higher peripheral neuropathy was higher during the taxane regimen and was notably reduced in the PTX group relative to controls (75% vs. 90.7%, P = 0.03), accompanied by an extended duration until grade 2 or higher neuropathy onset in the PTX arm (log-rank P < 0.0001). PTX significantly decreased the occurrence of grade 2 or higher mucositis during both the AC and taxane phases (P = 0.01 and P = 0.04, respectively) without causing notable differences in hematological toxicities or affecting cardiac, renal, or hepatic functions.ConclusionThe co-administration of PTX with AC/T chemotherapy in breast cancer patients significantly decreases the incidence and postpones the onset of grade 2 or higher peripheral neuropathy and the incidence of mucositis without causing additional risks for the patients.Clinical Trial RegistrationThe study was registered at https://clinicaltrials.gov/study/NCT06186700 (NCT06186700).